Reproductive Traits of Some Amphipods (Crustacea: Peracarida) in Different Habitats of Iran and Southern Caspian Sea - Mirzajani, Alireza; Sayadrahim, Mostafa; Sari, Alireza (International Journal of Zoology, 2011)
Reproductive traits of seven amphipods from northern parts of Iran at 11 localities were studied in order to find feasible species for usage in aquaculture industries. The results revealed that the breeding season for Gammarus lacustris and G. paricrenatus from high latitudes was limited to a few months from May to June. Breeding activity of G. komareki from some springs was observed throughout the year, while Obesogammarus acuminatus and G. aequicauda from southern wetlands of the Caspian sea and Pontogammarus maeoticus and P. borceae from southern Caspian sea shore showed various patterns. The mean egg number of O. acuminatus and G. aequicauda species was the highest with 49.8 and 37.7, respectively, while this value for G. komareki and P. maeoticus was the lowest with an average of 8.8 eggs. Reproductive strategy was found to be related to habitat characteristics such as chemical factors, substrate status, and the epifaunal living.